Pandemic information: a critical analysis of video viewing of institutional actions for deaf students - Pedrosa, Cleide Emilia Faye; Damaceno , Taysa Mércia dos Santos Souza; Abreu, Ricardo Nascimento; de Oliveira , Alzenira Aquino; Santos , Paulo Sérgio da Silva; Alves, Juliana Barbosa (Seven Editora, 2023)
The Critical Discourse Analysis (CDA) has the political-academic objective of analyzing the meanings of discourses, denouncing the vulnerability of social subjects. This chapter is the result of the research work plan PID9768-2021/UFS - CRITICAL STUDY OF DISCURSIVE AND SOCIAL PRACTICES OF SUBALTERN GROUPS: FROM TRAINING TO INFORMATION AND ITS UPDATE IN THE TIME OF COVID-19, whose general objective was to verify the institutional actions of federal public universities in Brazil (UFS and UFSC), in the initial period of the COVID-19 pandemic, with guidelines and information for the deaf public. Of a qualitative-interpretative nature, the research mapped the first informative videos about the pandemic that were made available to its deaf students. The theoretical and methodological contribution points out the stages of a research in CDA, based on the Sociological and Communicational Approach to Discourses (ASCD), namely: identifying the social problem that you want to research, understanding the context in which the social problem is inserted; formulate the objectives); the pre-analysis steps (defining the transdisciplinary interfaces and choosing the categories for analysis); the third step would be the analysis itself (verifying the meanings of social issues, establishing a link between discursiveness and its various semioses); Finally, we must reflect on the research done. In the research, the interpersonal and ideational metafunctions were observed. We included aspects of the situational context of LSF, considering the point of view of exclusion of the right to information that the deaf experienced. DOI: https://doi.org/10.56238/methofocusinterv1-081